GEOMETRI PROYEKTIF PG(2, pn) UNTUK MEMBENTUK RANCANGAN BLOK TIDAK LENGKAP SEIMBANG SIMETRIS - H, Yuni; Bambang, Irawanto (MATEMATIKA, 2008)
A Symmetric Balanced Incomplete Block design with parameters Â is Balanced Incomplete Block (BIB) design with Â and . Projective geometry PG (2, pn) is the finite geometry of two dimensions over the Galois Field GF(pn). Projective geometry PG (2, pn) can be used to construct symmetric BIB design if the points of PG(2, pn) are assumed same with the object of symmetric BIB design and the lines which contain the points from PG(2, pn) same with the blocks of symmetric BIB design. Â